Program “Pokjar Relina Berbasis Dunia Imajinasi” untuk Recovery Literasi dan Numerasi Anak pada Masa Pandemi Covid-19 di Desa Perbatasan (Desa Pacing Kecamatan Sukosewu Kabupaten Bojonegoro) - M. Zainudin; Doni Abdul Fatah; Zidni Alfian Barik; Muharram Brihan Harimurti; Agung Ridwan Asmaka (IKIP PGRI Bojonegoro, 2022)
ABSTRACTOne of the impacts of the COVID-19 pandemic is the occurrence of significant literacy and numeracy learning losses. This must be addressed immediately because literacy and numeracy are crucial abilities in the process of developing student’s capabilities. This community service aims to help restore children's literacy and numeracy during the COVID-19 pandemic in border villages (Pacing Village, Sukosewu District, Bojonegoro Regency). This community service is carried out in three stages, namely the initial, core, and final stages. The initial stage is carried out to explore the concrete problems faced by the students. The core stage is the application of fairy tale and pantomime-based learning with a cycle of planning, action, observation, and reflection. The final stage is carried out to report the implementation of the drawing to this community. The result of this activity is that the